Monitoring and modelling of the effects of process settings and screw geometry on melt pressure generation in polymer extrusion. (27th November 2012) - Abeykoon, Chamil; Li, Kang; Martin, Peter J.; Kelly, Adrian L.
Melt pressure is one of the most important process parameters in polymer extrusion and is closely related to product quality. However, it is not directly controllable and may be affected in a complex manner by changing other process operating conditions such as screw speed and barrel set temperatures. The ability to predict such parameters would be a powerful tool to aid process design and optimisation. However, only a few practical process models are currently available to predict melt pressure based on process settings in polymer extrusion. This paper describes new non–linear static and linear dynamic models that have been developed to explore the effects of process settings and screw geometry on melt pressure development in single screw extrusion. The models developed predict the melt pressure with good accuracy over a wide operating window. Investigations made using these models together with a frequency analysis of the measured signals showed that the melt pressure is influenced by both process settings and screw geometry.